Self-healable organic electrochemical transistor with high transconductance, fast response, and long-term stability - Ko, Jieun (2020)
The major challenges in developing self-healable conjugated polymers for organic electrochemical transistors (OECTs) lie in maintaining good mixed electronic/ionic transport and the need for fast restoration to the original electronic and structural properties after the self-healing process. Herein, we provide the first report of an all-solid-state OECT that is self-healable and possesses good electrical performance, by utilizing a matrix of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and a nonionic surfactant, Triton X-100, as a channel and an ion-conducting poly(vinyl alcohol) hydrogel as a quasi-solid-state polymer electrolyte. The fabricated OECT exhibits high transconductance (maximum 54 mS), an on/off current ratio of ∼1.5 × 103, a fast response time of 6.8 ms, and good operational stability after 68 days of storage. Simultaneously, the OECT showed remarkable self-healing and ion-sensing behaviors and recovered ∼95% of its ion sensitivity after healing. These findings will contribute to the development of high-performance and robust OECTs for wearable bioelectronic devices.